2003
DOI: 10.1021/ma0210980
|View full text |Cite
|
Sign up to set email alerts
|

Growth Rates and Morphologies of Miscible PCL/PVC Blend Thin and Thick Films

Abstract: Growth rates and morphologies of thin (0.1-2 µm) and thick (30 µm) films of miscible poly-( -caprolactone)/poly(vinyl chloride) (PCL/PVC) blends have been investigated. Under isothermal crystallization, PCL growth rates decrease in blend films thinner than 1 µm. However, in pure PCL films, no growth rate dependence is seen at the same thicknesses. In thick films of blends isothermally crystallized at a slow growth rate, two types of spherulites are observed with different growth rates and morphologies. One typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 26 publications
3
58
0
Order By: Relevance
“…According to the lamellae twisting theory suggested by Keith et al [28] that the formation of the ring-banded spherulites is attributed to the periodical lamellae twisting along the radical growths direction of the spherulites, we believed that the incorporation of the PLLA segments increased the twisting frequency of PTT lamellae and made the twisting of lamellae easier. Similar phenomenon has been reported in several polymer blends by Keith and coworkers [29], and it is found that 0.5 wt% of PVB lowers the onset banding temperature of PCL by 15 C. They believe it is due to the polar action of PVB on PCL, which increased the frequency of lamellar branching at screw dislocations and the intercrystalline connectivity of PCL. Similar phenomenon that introduction of PS block increased the helical twisting power and decreased the band spacing of PLLA ring-banded spherulites has been reported in block copolymer of PS-PLLA by Ho and coworkers [30].…”
Section: Spherulitic Morphologiessupporting
confidence: 85%
“…According to the lamellae twisting theory suggested by Keith et al [28] that the formation of the ring-banded spherulites is attributed to the periodical lamellae twisting along the radical growths direction of the spherulites, we believed that the incorporation of the PLLA segments increased the twisting frequency of PTT lamellae and made the twisting of lamellae easier. Similar phenomenon has been reported in several polymer blends by Keith and coworkers [29], and it is found that 0.5 wt% of PVB lowers the onset banding temperature of PCL by 15 C. They believe it is due to the polar action of PVB on PCL, which increased the frequency of lamellar branching at screw dislocations and the intercrystalline connectivity of PCL. Similar phenomenon that introduction of PS block increased the helical twisting power and decreased the band spacing of PLLA ring-banded spherulites has been reported in block copolymer of PS-PLLA by Ho and coworkers [30].…”
Section: Spherulitic Morphologiessupporting
confidence: 85%
“…This shows that the extinction-banded spherulites possess an identically-continuous feature of radial lamellar packing behavior with those of common compact polymer spherulites, e.g., the situations illustrated in Figure 14, so the uniform spherulite radial growth results. This point is similar to the cases of melt-crystallization [56]. The most interesting feature of the spherulitic growth behavior in the evaporative crystallization of polymer solution-cast films is the thickness dependence of radial growth velocity.…”
Section: Classical Extinction Banded Spherulitessupporting
confidence: 77%
“…It is obvious that The most interesting feature of the spherulitic growth behavior in the evaporative crystallization of polymer solution-cast films is the thickness dependence of radial growth velocity. It is generally reported that when polymer spherulites are generated from the molten films, the radial growth rate first increases with increasing film thickness and then holds a constant value [56]. However, the cases in the evaporative crystallization are directly opposite.…”
Section: Classical Extinction Banded Spherulitesmentioning
confidence: 99%
“…11 The miscibility of PCL with PVC was extensively investigated using DSC and these materials were found to be miscible. 20,21 The miscibility of PVAC and PVC was also investigated by DSC and their miscibility depends on the solvent used during solution blending.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%